Constructive and geographical value of landscape and technical systems research - Лаврик, Олександр Дмитрович; Цимбалюк, Валентина Василівна (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
The aim of the research is to reveal the constructive and geographical significance of landscape and technical systems research which involves development of sequential actions to assess the state of the block structure, identification of stages, choice of development options and final optimization.Methods. The study is based on the use of a systemic and model paradigm in geography. The specific character of the expert group’s work with landscape and technical systems is shown on the example of the research algorithm development.Scientific novelty of the article is universality of the proposed algorithm of research actions in relation to any landscape and technical system.Practical value is determined by the development of assessment methods, options and ways to optimize landscape and technical systems that are at the stage of «destruction».Research results. It is noted that each stage of such studies provides for a detailed analysis of the block structure of the landscape and technical system and its interrelations with the environment. The best is the activity of an expert group of four researchers. Three participants (experts in the national economy) will analyze the blocks and one of them (the landscape engineer) will coordinate their actions.The first stage of the research is to assess the state of each individual block of the landscape and technical system (control, technical and natural block). Research results of a certain landscape and technical system are proposed to be formalized using method of expert assessments. The main criteria are selected in the formation of evaluation tables, taking into account the specificity of each block of the system.The second stage of research involves identification of the landscape and technical system’s development stage. According to the evaluation of blocks a summary table is formed and the results are added. The development stage is determined based on the ratio of individual blocks average scores of the landscape and technical system.At the third stage, a choice of possible further development of the landscape and technical system is made. Six variants of development have been considered, each of which is focused on the activity of the control unit. Variant A: the landscape and technogenic system is completely left without any control, its development goes by natural laws. Variant B1: it is proposed to restore partial control over the landscape and technogenic system. Variant B2: the landscape and technogenic system completely changes the functional purpose and is used for recreation. Variant B3: landscape and technogenic systems are used as microkernels for communicating ecological corridors in river valleys. Variant C1: the system is restored to its original state. Variant C2: restoration of control is aimed at changing the functional purpose of the former landscape and technical system and carrying out its new construction.Optimization begins at the last stage of the research when a set of measures aimed at restoring the work of the landscape and technical system is carried out.The conclusion is made that in such studies the primary role is assigned to landscape engineers, since the future vital activity of landscape and technical systems will depend on their universal knowledge, skills and habits.